Psychological resources and interventions for teachers’ emotional competence and well-being: a systematic review - Cervellione, Brenda; Lombardo, Ester Maria Concetta; Iacolino, Calogero (Frontiers in Psychology, 2025)
IntroductionTeachers are increasingly exposed to emotional and organizational stressors that affect their psychological well-being and professional functioning. Emotional Intelligence (EI) and Reflective Functioning (RF) have emerged as key protective factors in preventing burnout and promoting Quality of Life (QoL) in educational contexts.MethodsThis systematic review followed the PRISMA 2020 guidelines and synthesized findings from 42 empirical studies published between 2010 and 2024. Studies were identified through comprehensive searches of EBSCOhost, PubMed, and Google Scholar. Both psychological interventions and observational studies exploring the relationship between EI, RF, and teacher well-being were included.ResultsIntervention studies showed that programs targeting emotional regulation, mindfulness, and reflective capacity significantly improved teachers’ emotional competencies and psychological resilience. Observational studies further supported the role of EI and RF in reducing burnout and enhancing QoL, while also highlighting the influence of personality traits and contextual moderators. However, methodological heterogeneity, limited use of longitudinal designs, and variation in outcome measures constrained generalizability.DiscussionFindings underscore the importance of promoting psychological resources and structured interventions to support teachers’ emotional well-being and professional sustainability. Future research should prioritize standardized, longitudinal, and culturally sensitive approaches to better inform evidence-based practice in educational settings.